Dyads of GGC and GCC form hotspot colonies that coincide with the evolution of human and other great apes - M. Arabfard; N. Tajeddin; S. Alizadeh; M. Salesi; H. Bayat; H. R. Khorram Khorshid; S. Khamse; A. Delbari; M. Ohadi (BMC Genomic Data, 2024)
Abstract Background GGC and GCC short tandem repeats (STRs) are of various evolutionary, biological, and pathological implications. However, the fundamental two-repeats (dyads) of these STRs are widely unexplored. Results On a genome-wide scale, we mapped (GGC)2 and (GCC)2 dyads in human, and found monumental colonies (distance between each dyad < 500 bp) of extraordinary density, and in some instances periodicity. The largest (GCC)2 and (GGC)2 colonies were intergenic, homogeneous, and human-specific, consisting of 219 (GCC)2 on chromosome 2 (probability < 1.545E-219) and 70 (GGC)2 on chromosome 9 (probability = 1.809E-148). We also found that several colonies were shared in other great apes, and directionally increased in density and complexity in human, such as a colony of 99 (GCC)2 on chromosome 20, that specifically expanded in great apes, and reached maximum complexity in human (probability 1.545E-220). Numerous other colonies of evolutionary relevance in human were detected in other largely overlooked regions of the genome, such as chromosome Y and pseudogenes. Several of the genes containing or nearest to those colonies were divergently expressed in human. Conclusion In conclusion, (GCC)2 and (GGC)2 form unprecedented genomic colonies that coincide with the evolution of human and other great apes. The extent of the genomic rearrangements leading to those colonies support overlooked recombination hotspots, shared across great apes. The identified colonies deserve to be studied in mechanistic, evolutionary, and functional platforms.